Testing of code-based pseudorandom number generators for post-quantum application - Кузнецов, О.О.; Кіян, А.С.; Пушкарьов, А.І.; Кузнецова, Т.Ю. (Radiotekhnika, 2020)
Recent advances in quantum computing based on new principles and phenomena of quantum mechanics show that quantum cryptanalysis of modern cryptographic algorithms can become real in the coming years. For example, according to the forecasts of the US National Institute of Standards and Technology (NIST) in the next decade, quantum cryptanalysis of most asymmetric cryptosystems used today will be available. For this reason, NIST announced a contest of post-quantum (i.e., resistant to quantum cryptanalysis) cryptographic algorithms for directional encryption, electronic signature, and key encapsulation. In the coming years, standardization of the selected algorithms and their early implementation is expected. Obviously, other cryptographic algorithms, for example, pseudorandom number generators based on solving complex theoretical problems (discrete logarithm, factorization, etc.), will also be subject to further revision. These generators must also be replaced by reliable and safe algorithms suitable for use even in the conditions of the possible application of quantum cryptanalysis (i.e., in the post-quantum period). This paper is devoted to the study of provably secure generators whose resistance is based on the complexity of solving the syndrome decoding problem. This structure allows the generators to keep the resistance to both classical cryptanalysis and cryptanalysis using quantum computing. The design features of classic code-based generator representative proposed by Fisher and Stern are presented, and a new generator scheme is proposed to overcome the drawback of its predecessor, such as a reduced practical maximum period length, by using a linear feedback shift register. Within this paper Results of heuristic testing of the above-mentioned generators is conducted in terms of the sequence period, the speed of sequence generation, the cryptographic resistance of the generators and the possibility of their use in the post-quantum period.